The Easterlin Paradox - Richard A. Easterlin; Kelsey J. O'Connor (Institute of Labor Economics (IZA), 2020)
The Easterlin Paradox states that at a point in time happiness varies directly with income, both among and within nations, but over time the long-term growth rates of happiness and income are not significantly related. The principal reason for the contradiction is social comparison. At a point in time those with higher income are happier because they are comparing their income to that of others who are less fortunate, and conversely for those with lower income. Over time, however, as incomes rise throughout the population, the incomes of one's comparison group rise along with one's own income and vitiates the otherwise positive effect of own-income growth on happiness. Critics of the Paradox mistakenly present the positive relation of happiness to income in cross-section data or in short-term time fluctuations as contradicting the nil relation of long-term trends.
Keywords: I31; D60; O10; O5; 330; Easterlin Paradox; economic growth; income; happiness; life satisfaction; subjective well-being; long-term; short-term; trends; fluctuations; transition countries; less developed countries; developed countries